1999
DOI: 10.1002/(sici)1098-2345(199912)49:4<285::aid-ajp1>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

What is a marmoset?

Abstract: Callitrichid primates typically give birth to twin offspring that are somatic chimeras of cells derived from two products of conception. Each individual is thus the phenotype of two sibling genotypes, one of which may be more closely related to the germ line of the individual's parents than to the individual's own germ line. Chimerism could therefore help to explain the evolution of alloparental care and social suppression of reproduction in callitrichids. Placental chimerism may also have important implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 50 publications
0
42
0
1
Order By: Relevance
“…Female callitrichids are polyovulatory and dizygotic twinning is the rule, but singleton births, triplets, and even quadruplets occur (Tardif et al, 2003. Blood chimerism occurs in callitrichids due to placental vascular anastomoses (Haig, 1999). Female callitrichid species avoid becoming freemartins in utero as often occurs with twinning in cattle via an effective aromatizing enzyme system, which converts androgens to estrone (Ryan et al, 1961).…”
Section: Reproductionmentioning
confidence: 99%
“…Female callitrichids are polyovulatory and dizygotic twinning is the rule, but singleton births, triplets, and even quadruplets occur (Tardif et al, 2003. Blood chimerism occurs in callitrichids due to placental vascular anastomoses (Haig, 1999). Female callitrichid species avoid becoming freemartins in utero as often occurs with twinning in cattle via an effective aromatizing enzyme system, which converts androgens to estrone (Ryan et al, 1961).…”
Section: Reproductionmentioning
confidence: 99%
“…From an evolutionary perspective, engrafted cells are extensions of the genetic individual of whom the cells are disjunct fragments and are predicted to evolve effects that increase that individual’s inclusive fitness [19]. I previously suggested that engrafted fetal cells could manipulate the mother’s body for offspring benefit [20] and now develop that idea further.…”
Section: Collective Bodiesmentioning
confidence: 99%
“…As an animal model of non-human primates, the common marmoset (Callithrix jacchus), a New World monkey, has been used in a variety of biomedical studies that have ranged in topic from reproductive medicine to social behavioral science (Heig, 1999;Norscia and Palagi, 2011;Ash and Buchanan-Smith, 2014). The inevitable evolution of gene manipulation technologies means that the use of the common marmoset in these research fields will increase (Sasaki et al, 2005), Moreover, since genome of this species has been recently sequenced, it is anticipated that there will be rapid surge in the interest of primate biology (Marmoset Genome Sequencing and Analysis Consortium and Marmoset Genome Sequencing and Analysis Consortium, 2014).…”
Section: Introductionmentioning
confidence: 99%